Activated-platelet targeting of CD39 as a potential way forward - Hohmann, J. D.; Peter, K. (Hämostaseologie, 2016)
Antiplatelet therapy is given to millions of patients and has saved numerous lives. However, it is also associated with complications including fatal bleedings. Clinically used antiplatelet drugs seem to follow the rule of an inherent link of improved anti-thrombotic potency with increased risk of bleeding complications. Therefore, there is an ongoing quest to develop drugs that are able to break this link that has prevented many patients from receiving antiplatelet protection and has resulted in substantial mortality and morbidity. We describe a new antiplatelet approach that is based on an recombinant antibody protein, a drug format that has recently attracted major interest. Two unique components are genetically combined in this molecule: 1) The ecto-nucleoside triphosphate diphosphohydrolase NTPDase CD39, which enzymatically degrades ATP and ADP to AMP, which is then further degraded to adenosine by the endothelially expressed CD73. Thereby, the platelet activating ADP is reduced and replaced by the platelet inhibiting adenosine resulting in a strong antiplatelet effect. 2) A single-chain antibody (scFv) that specifically binds to the activated GPIIb/IIIa receptor and thus allows targeting to activated platelets. The described fusion protein results in strong enrichment of CD39’s antiplatelet effect, resulting in potent inhibition of platelet adhesion and aggregation and thrombosis in mice. The activated platelet targeting allows using a low systemic concentration that does not interfere with normal haemostasis and thus does not cause bleeding time prolongation in mice. Conclusion: We describe a new antiplatelet approach that promises to deliver strong localized antithrombotic effects without associated bleeding problems.Anti-thrombozytäre Medikamente wurden und werden von Millionen Patienten eingenommen und haben unzählige Leben gerettet. Gleichzeitig gehen sie aber mit Komplikationen einher, z. B. tödliche Blutungen. Die klinisch eingesetzten anti-thrombozytären Medikamente scheinen der Regel zu folgen, die besagt, dass eine verbesserte anti-thrombozytäre Therapie zwangsweise mit vermehrten Blutungen einhergeht. Somit besteht ein dringlicher Bedarf Medikamente zu entwickeln, die diesen Zusammenhang wiederlegen. Wir beschreiben einen neuen anti-thrombozytären Ansatz auf der Grundlage eines rekombinanten Antikörpers, ein therapeutisches Format, das im Mittelpunkt vieler pharmazeutischer Neuentwicklungen steht. Zwei einzigartige Komponenten sind genetisch miteinander verbunden: 1) Die Ektonucleosid-triphosphat-Diphosphohydrolase NTPDase CD39, die ATP und ADP zu AMP umsetzt, das weiter zu Adenosine durch endotheliales CD73 umgewandelt wird. Dadurch wird die Konzentration des Thrombozyten-aktivierenden ADP reduziert und dies wird durch das Thrombozyten-hemmende Adenosine ersetzt. Dies resultiert in einer effizienten Hemmung der Thrombozyten. 2) Ein Single-chain-Antikörper (scFv), der spezifisch an den aktivierten GPIIb/IIIa-Rezeptor bindet und dadurch ein Targeting zu aktivierten Thrombozyten ermöglicht. Das beschriebene Fusionsmolekül ermöglicht eine Anreicherung des CD39 an aktivierten Thrombozyten und dadurch eine effiziente Hemmung der Thrombozytenadhäsion und -aggregation und letztendlich auch Thrombusbildung in der Maus. Das Targeting zu aktivierten Thrombozyten erlaubt die Verwendung einer geringen systemischen Konzentration, die keine Verlängerung der Blutungszeit in der Maus hervorruft und somit die Hämostase nicht beeinflusst. Schluss-folgerung: Wir konnten einen neuen antithrombozytären Ansatz beschreiben, der potente Thrombozytenhemmung ohne Blutungskomplikationen verspricht.
Keywords: Antiplatelet drugs